Discriminating between Virtues: The Virtue of Friendship according to Aristotle - Salamouras, Georgios (Conatus - Journal of Philosophy, 2018)
According to Aristotle, those habits that are worthy of praise are defined as virtues. They are divided into two categories, intellectual and moral. According to the philosopher, friendship is considered the ultimate virtue, superior even to justice. This paper seeks to provide a detailed analysis of the Aristotelian account on friendship, focusing on Aristotle's claim that friendship provides the strongest ties between citizens and, therefore, a coherent bond for cities.